Role of the ATP-Binding Domain of the Human Papillomavirus Type 11 E1 Helicase in E2-Dependent Binding to the Origin - Titolo, Steve (American Society for Microbiology, 1999)
Replication of the genome of human papillomaviruses (HPV) is initiated by the recruitment of the viral E1 helicase to the origin of DNA replication by the viral E2 protein, which binds specifically to the origin. We determined, for HPV type 11 (HPV-11), that the C-terminal 296 amino acids of E1 are sufficient for interaction with the transactivation domain of E2 in the yeast two-hybrid system and in vitro. This region of E1 encompasses the ATP-binding domain. Here we have examined the role of this ATP-binding domain, and of ATP, on E2-dependent binding of E1 to the origin. Several amino acid substitutions in the phosphate-binding loop (P loop), which is implicated in binding the triphosphate moiety of ATP, abolished E2 binding, indicating that the structural integrity of this domain is essential for the interaction. The structural constraints imposed on the E1 P loop may differ between HPV-11 and bovine papillomavirus type 1 (BPV-1), since the P479S substitution that inactivates BPV-1 E1 is tolerated in the HPV-11 enzyme. Other substitutions in the E1 P loop, or in two other conserved motifs of the ATP-binding domain, were tolerated, indicating that ATP binding is not essential for interaction with E2. Nevertheless, ATP-Mg stimulated the E2-dependent binding of E1 to the origin in vitro. This stimulation was maximal at the physiological temperature (37°C) and did not require ATP hydrolysis. In contrast, ATP-Mg did not stimulate the E2-dependent binding to the origin of an E1 protein containing only the C-terminal domain (353 to 649) or that of mutant E1 proteins with alterations in the DNA-binding domain. These results are discussed in light of a model in which the E1 ATP-binding domain is required for formation of the E2-binding surface and can, upon the binding of ATP, facilitate and/or stabilize the interaction of E1 with the origin.